DEVELOPMENT OF EARLY READING TEACHING COMPETENCE FOR PRESCHOOL TEACHERS THROUGH TRAINING IN MAKING READING CARDS FROM USED MATERIALS - Syarifah Zainab; Julia Aridhona; Hanna Amalia (Universitas Muhammadiyah Aceh, 2024)
Early Childhood Education Programs teachers (PAUD) should have high creativity in developing their students' teaching competence, this is because PAUD students have very high imagination. However, the limited knowledge and teaching facilities of PAUD teachers, especially those who teach in the regions, mean that PAUD teachers run out of ideas for developing teaching creativity. One of the teaching competencies of PAUD teachers is providing interesting and fun learning media for students. Several types of training that have been provided by teachers have only been attended by representatives from each PAUD, so that the information and knowledge obtained is not evenly shared by all PAUD teachers in the region. Referring to this problem, the community service activity that will be carried out is to create an innovation training in making learning media for early reading cards (flashcards) to improve the competence of teaching early reading for PAUD teachers. The location of this activity will be in Lampanah Teungoh Village, Aceh Besar. The output target to be achieved is that teachers master the material well, understand the material and are able to apply it to students. Apart from that, participants are able to create their own early reading learning media and are able to teach it to students. Keywords: Teaching Competency; PAUD Teacher; Learning Media; Early Reading